Interpretation of Gender Verses According to Imam Al-Tabarī and Asma Barlas: A Comparative Study - Aminah, Siti; Rohmana, Jajang A. (International Journal of Nusantara Islam, 2025)
This study discusses the differences in interpretation of gender verses in Islam based on the interpretation of Jāmi’ al-Bayān by Imam al-Ṭabarī and Believing Women in Islam by Asma Barlas. The main focus of this study is the analysis of Qs. An-Nisā’ [4]: 1 on the creation of women, Qs. An-Nisā’ [4]: 3 on polygamy, and Qs. An-Nisā’ [4]: 34 on male leadership and nusyuz. This study uses the muqāran (comparative) interpretation method and Hans-Georg Gadamer’s hermeneutic theory to understand the differences in their perspectives in interpreting gender verses. The results of the study show that al-Ṭabarī uses the bi al-ma’tsur interpretation approach based on history and traditional understanding, so that his interpretation tends to be textual and maintains patriarchal norms in gender relations. In contrast, Asma Barlas criticized the approach by using critical hermeneutics to interpret the Qur'an as a book that upholds gender equality and rejects interpretations that support the patriarchal system. Analysis using Gadamer's Fusion of Horizons theory shows that these differences in interpretation are influenced by historical, social, and epistemological factors. Al-Ṭabarī lived in a society that still had a strong patriarchal system, while Asma Barlas interpreted gender verses in a modern academic context with the influence of feminism and critical studies of religious texts. This study concludes that gender interpretation in Islam should not only adhere to a textual approach but also consider social, cultural, and historical aspects to be more relevant to the values of justice and equality in Islam. This study is expected to contribute to the development of gender interpretation studies in Islam and provide new insights into a more inclusive approach to interpreting the Qur'an.